2018
DOI: 10.1016/s2214-109x(18)30373-5
|View full text |Cite
|
Sign up to set email alerts
|

Filtered sunlight versus intensive electric powered phototherapy in moderate-to-severe neonatal hyperbilirubinaemia: a randomised controlled non-inferiority trial

Abstract: Thrasher Research Fund and National Center for Advancing Translational Sciences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Although filtered sunlight may be an option, direct sunlight is not safe due to the high levels of infrared and UV radiation that could lead to overheating, dehydration and sunburn. Therefore, sunlight PT is not recommended when electric powered PT is available [5,11,15]. Again this may reflect a discrepancy between the development of the level of health care in Indonesia and alternative methods that could be used in circumstances with fewer medical resources [15].…”
Section: Questions and Answers Hospitalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although filtered sunlight may be an option, direct sunlight is not safe due to the high levels of infrared and UV radiation that could lead to overheating, dehydration and sunburn. Therefore, sunlight PT is not recommended when electric powered PT is available [5,11,15]. Again this may reflect a discrepancy between the development of the level of health care in Indonesia and alternative methods that could be used in circumstances with fewer medical resources [15].…”
Section: Questions and Answers Hospitalsmentioning
confidence: 99%
“…Therefore, sunlight PT is not recommended when electric powered PT is available [5,11,15]. Again this may reflect a discrepancy between the development of the level of health care in Indonesia and alternative methods that could be used in circumstances with fewer medical resources [15].…”
Section: Questions and Answers Hospitalsmentioning
confidence: 99%
“…A recent Cochrane review has evaluated the evidence from randomized controlled trials that compared using filtered sunlight versus conventional phototherapy for treating hyperbilirubinaemia in term or near-term newborn infants [11]. The authors identified two trials with 621 infant participants in total [12, 13]. These were conducted by the same research teams in Nigeria during the 2010s, and assessed as the primary outcome whether filtered sunlight was non-inferior to (not worse than) conventional phototherapy for reducing the rate of rise of serum bilirubin levels.…”
Section: Commentarymentioning
confidence: 99%
“…Although widely used, the technique used in phototherapy is not equally accessible in all locations, as it requires a high financial resource, so the use of filtered sunlight has been studied in its effectiveness and safety, both of which have been proven by Slusher et al ( , 2018. In the same line of minimizing costs with the treatment of neonatal jaundice, Yilmaz et al (2015) present a model of home phototherapy with LED, which demonstrated levels of reduction of bilirubin, as long as it is less than or equal to 20mg / dL [24][25][26] .…”
Section: (Citation Of the Review Articles) Corroborating What Is Already Recommended By The Americanmentioning
confidence: 99%